Abundance of Secreted Proteins of Trichoderma reesei Is Regulated by Light of Different Intensities - Stappler, Eva; Walton, Jonathan D.; Beier, Sabrina; Schmoll, Monika (Frontiers in Microbiology, 2017)
In Trichoderma reesei light is an important factor in the regulation of glycoside hydrolase gene expression. We therefore investigated the influence of different light intensities on cellulase activity and protein secretion. Differentially secreted proteins in light and darkness as identified by mass spectrometry included members of different glycoside hydrolase families, such as CBH1, Cel3A, Cel61B, XYN2 and XYN4. Several of the associated genes showed light-dependent regulation on the transcript level. Deletion of the photoreceptor genes blr1 and blr2 resulted in a diminished difference of protein abundance between light and darkness. The amount of secreted proteins including that of the major exo-acting beta-1,4-glucanases CBH1 and CBH2 was generally lower in light-grown cultures than in darkness. In contrast, cbh1 transcript levels increased with increasing light intensity from 700 to 2000 lux but dopped at high light intensity (5000 lux). In the photoreceptor mutants Δblr1 and Δblr2 cellulase activity in light was reduced compared to activity in darkness, showing a discrepancy between transcript levels and secreted cellulase activity. Furthermore, evaluation of different light sensitivities revealed an increased light tolerance with respect to cellulase expression of QM9414 compared to its parental strain QM6a. Investigation of one of the differentially expressed proteins between light and darkness, CLF1, revealed its function as a factor involved in regulation of secreted protease activity. T. reesei secretes a different set of proteins in light compared to darkness, this difference being mainly due to the function of the major known photoreceptors. Moreover, cellulase regulation is adjusted to light intensity and improved light tolerance was correlated with increased cellulase production. Our findings further support the hypothesis of a light intensity dependent posttranscriptional regulation of cellulase gene expression in T. reesei.